The Effect Of Intellectual Capital Efficiency On Company’s Market Value With Company’s Financial Performance As Intervening Variables - Khrisna Adisatya Sujati; Indira Januarti (Jurnal Reviu Akuntansi dan Keuangan, 2021)
The purpose of this study is to investigate empirically the relation between the company’s intellectual capital efficiency and company’s market valuation with company’s financial performance as intervening variables. This study using data from the Indonesia listed service companies. The samples of this study was 109 companies. Pulic’s Value Added Intellectual Coefficient (VAICTM) used as the efficiency measure of company’s intellectual capital. The authors construct regression models to examine the relationship between company’s intellectual capital efficiency and company’s market valuation and explore the relation with company’s financial performance as intervening variables. The results support the hypothesis that company’s intellectual capital has an affect on company’s market valuation. In addition, the authors found that company’s financial performance has a role as full mediator on the relation between the company’s intellectual capital efficiency and company’s market valuation. This study results can be used as a reference for companies’ management to improve their efficiency of the intellectual capital so the company's financial performance and value can be improved.